'So much Gaelic to me': Beckett and the Irish Language. Issue 2 (September 2015) - Graham, Alan
Abstract : This essay explores the ways in which Ireland's sacralised national language figures in Beckett's work. Oblique references to Irish in the Beckett oeuvre are read against a history of Anglo-Irish investment in the language as a mode of 'impatriation', a means by which to circumscribe anxieties surrounding an identity fraught with socio-political anomalies. In addition, the suspicion of 'official language' in Beckett's work is considered in light of his awareness of the 'language issue' in his native country, particularly in relation to the powerful role of the Irish language in the reterritorialisation of the civic sphere in post-independence Ireland.